Sitting position affects performance in cross-country sit-skiing - Lund Ohlsson, M.; Laaksonen, M. S. (European Journal of Applied Physiology, 2017)
Purpose: In cross-country sit-skiing (XCSS), athletes with reduced trunk control predominantly sit with the knees higher than the hips (KH); a position often associated with large spinal flexion. Therefore, to improve spinal curvature a new sledge with frontal trunk support, where knees are lower than hips (KL) was created. It was hypothesized that the KL position would improve respiratory function and enhance performance in seated double-poling compared to KH. Methods: Ten female able-bodied cross-country skiers (age 25.5 ± 3.8 years, height 1.65 ± 0.05 m, mass 61.1 ± 6.8 kg) completed a 30 s all-out test (WIN), a submaximal incremental test including 3-7 3 min loads (SUB) and a maximal 3 min time trial (MAX) in both KL and KH positions. During SUB and MAX external power, pole forces, surface electromyography, and kinematics were measured. Metabolic rates were calculated from oxygen consumption and blood lactate concentrations. Results: KL reduced spinal flexion and range of motion at the hip joint and indicated more muscle activation in the triceps. Performance (W kg-1) was impeded in both WIN (KH 1.40 ± 0.30 vs. KL 1.13 ± 0.33, p < 0.01) and MAX (KH 0.88 ± 0.19 vs. KL 0.67 ± 0.14, p < 0.01). KH resulted in higher gross efficiency (GE) and lower lactate concentration, anaerobic metabolic rate, and minute ventilation for equal power output. Conclusions: The new KL position can be recommended due to improved respiratory function but may impede performance. Generalization of results to XCSS athletes with reduced trunk muscle control may be limited, but these results can serve as a control for future studies of para-athletes.